What are the comparative outcomes of laparoscopic versus open surgical techniques in the management of intestinal obstruction in adult patients? : A Systematic Review - Ruditya Lukman Hakim; Rezky Putri Wahyu Agustine (The International Journal of Medical Science and Health Research, 2025)
Introduction: Intestinal obstruction is a common surgical emergency traditionally managed by open laparotomy. While laparoscopic surgery has emerged as an alternative with documented short-term benefits, gaps remain, particularly concerning long-term outcomes like recurrence and reoperation rates. This systematic review evaluates the comparative outcomes of laparoscopic versus open surgery for intestinal obstruction in adults to consolidate current evidence and inform clinical practice. Methods: This review followed PRISMA 2020 guidelines. A comprehensive search was conducted across PubMed, Springer, Google Scholar, and other databases for studies published since 2015 comparing laparoscopic and open surgery for intestinal obstruction in adults. Twenty-five studies, including RCTs, cohort studies, and meta-analyses, were selected. Data on operative metrics, recovery outcomes (length of stay, return of bowel function), complications, mortality, and patient-centered outcomes were extracted and synthesized. Results: The synthesis of evidence consistently showed that laparoscopic surgery is associated with significant short-term benefits. These include shorter hospital stays (reported in 17 studies), faster recovery of bowel function (9 studies), lower overall complication rates (20 studies), and reduced intraoperative blood loss (5 studies). Mortality was also generally lower in the laparoscopic group. However, data on operative time was conflicting, and long-term outcomes such as obstruction recurrence and reoperation rates were infrequently and inconsistently reported. Conclusion: Laparoscopic surgery is superior to open surgery for managing intestinal obstruction in adults regarding short-term outcomes, demonstrating clear advantages in recovery, safety, and efficiency. Despite these benefits, a significant evidence gap exists for long-term outcomes. While laparoscopy should be the preferred initial approach, further high-quality, long-term research is needed to solidify its role as the definitive standard of care.